Optimizing the Role of Teachers and Educators in Realizing Quality Character-Based Education in the Digital Age - Raysa Afifa Amelia; Sakina Radhtul Easy; Shitra Giofika; Rinda Handayani Fathuloh; Ririn Mardana Putri; Selfi Regina Putri; Salsabila; Annisaul Khairat (Yayasan Pendidikan Haiba Nasywa in cooperation with Pesantren Wahdatul Ulum Internasional, 2025)
The advancement of digital technology necessitates fundamental transformation in educational practices, particularly regarding the roles of teachers and educational staff. This literature study examines optimization strategies for teachers and educational personnel in realizing quality character-based education amid digital transformation. Through thematic content analysis of recent academic publications, this research reveals three critical findings. First, 60% of teachers possess minimal digital competencies, requiring structured capacity building through tiered training and peer mentoring programs. Second, effective digital education integration demands a three-pillar model comprising professional digital competencies, character-based innovative learning, and educational ecosystem synergy. Third, educational staff including school principals, digital librarians, and laboratory technicians play strategic yet often overlooked roles in creating conducive digital learning environments. The study demonstrates that successful digital education depends not merely on technological sophistication but on educators' capacity to utilize technology as instruments for enhancing learning quality while maintaining character values. This research contributes a comprehensive framework emphasizing the balance between technological mastery and moral value cultivation, proposing systematic professional development programs and multi-stakeholder collaboration to address implementation barriers including digital gaps, infrastructure limitations, and increased workload burdens.